MUSIC AND SOCIETY: संगीत एवं समाज - Gupta, Shuchi (International Journal of Research -GRANTHAALAYAH, 2015)
The shloka presented in the musical text ’Swar Mel Kalanidhi’ indicates the infinity of musical art in creation. Music pervades Indian society from a time when societies were not even fully developed. Mother Goddess Saraswati, the Goddess of knowledge for human welfare, sent this Goddess art to Bhuloka through Narada. Since then, uninterrupted streams of music and society have been continuously flowing at the same pace, seeking shelter from each other. Society is an indispensable and basic structure for a person, under whose shelter he shares his ethics, customs, rituals, beliefs and traditions, etc. In the form of redemption, the society provides protective armor to the person. Through speech and arts, he remains strongly connected to society through expressions. This sequence is going on continuously. When he was in a wild state, he was still a social animal and lived in a herd. Even in the absence of language, by playing hand-foot with gestures and gestures, stones were exchanged in a musical manner by playing stones. Over time, the herds changed into society and musical art also developed. This is to say that the development process of society and music has moved along to the present form. संगीत ग्रन्थ ‘स्वर मेल कलानिधि‘ में वर्णित प्रस्तुत श्लोक सृष्टि में संगीत कला की अनन्तता को दर्शाता है। भारतीय समाज में संगीत उस समय से व्याप्त है जब समाज पूर्ण रूप से विकसित भी नहीं हुए थे। मानव कल्याण हेतु ज्ञान की देवी माँ सरस्वती ने नारद जी के माध्यम से इस देवी कला को भूलोक में भेजा था। तभी से संगीत एवं समाज रूपी अविरल धाराएं एक-दूसरे से आश्रय पाते हुए निरन्तर समान गति से बह रही है। समाज व्यक्ति के लिए एक अनिवार्य एवं आधारभूत ढांचा है जिसके आश्रय में वह अपने आचार-विचार, रीति-रिवाज, संस्कार, मान्यताएं एवं परम्परराएं आदि सांझा करता है, प्रतिदान स्वरूप समाज व्यक्ति को सुरक्षात्मक कवच प्रदान करता है। वाणी एवं कलाओं के माध्यम से भावभिव्यक्ति द्वारा वह समाज से दृढ़ता से जुड़ा रहता है। यह क्रम यू ही निरन्तर चला आ रहा है। जब वह जंगली अवस्था में था तब भी वह सामाजिक प्राणी था और झुण्डो में रहता था। भाषा के अभाव में भी संकेतों एवं भाव-भंगिमाओं के साथ हस्त-पाद संचालन द्वारा पत्थरों को बजाकर संगीतमय तरीके से भावों का आदान-प्रदान करता था। समय के साथ-साथ झुण्ड समाज में परिवर्तित हो गए और संगीत कला भी विकसित होती गई। कहने का तात्पर्य यह है कि समाज एवं संगीत की विकास प्रक्रिया साथ-साथ चलते हुए वर्तमान स्वरूप तक पहुंची है।